Review of selected research in applied linguistics published in Australia (2008-2014) - Oliver, Rhonda; Chen, H.; Moore, S. (2016)
This article reviews the significant and diverse range of research in applied linguistics published in Australia in the period 2008-2014. Whilst acknowledging that a great deal of research by Australian scholars has been published internationally during these seven years, this review is based on books, journal articles, and conference proceedings published in Australia. Many of these sources will be unfamiliar to an international audience, and the purpose of this article is to highlight this body of research and the themes emerging from it. The journals selected in this review include Australian Journal of Language and Literacy, Australian Review of Applied Linguistics (ARAL), BABEL, English in Australia, English Australia, Papers in Language Testing and Assessment, Prospect: An Australian Journal of TESOL, TESOL in Context, and University of Sydney Papers in TESOL. Selected refereed proceedings are from key national conferences including: ALAA (Applied Linguistics Association of Australia), ACTA (Australian Council of TESOL Association), ASFLA (Australian Systemic Functional Linguistics Association), and ALS (Australian Linguistics Society). Our review of selected applied linguistics work revolves around the following themes: the responses to the needs of government planning and policy; the complexity of Australia's multicultural, multilingual society; the concern for recognizing context and culture as key factors in language and language learning; social activism in supporting language pedagogy and literacy programmes at all levels of education; and acknowledgement of the unique place held by Indigenous languages and Aboriginal English in the national linguistic landscape.